Perkembangan Kerajaan Allah di Kalimantan Tengah - Candra Junika; Revalina Revalina; Deci Natalia; Sarmauli Sarmauli (Sukacita : Jurnal Pendidikan Iman Kristen, 2025)
This study examines the spread of Christianity by the Kingdom of God in Central Kalimantan, focusing on its history, challenges, and impact on local communities. Using a qualitative approach with a descriptive-analytical method, data were collected through interviews, observations, and document studies. The analysis was conducted using Miles and Huberman’s interactive model, including data reduction, data presentation, and conclusion drawing. The findings indicate that the spread of Christianity by the Kingdom of God was influenced by social, cultural, and political factors. The main challenges included local cultural resistance, social dynamics, and changing government policies. However, the teachings and values established have persisted in society to this day. These findings provide new insights into the interaction between religion and culture in the local historical context and its contribution to community identity. The implications of this research can serve as a reference for understanding religious dissemination patterns and preserving religious values amidst social changes.